Low-carbon high-performance self-sensing geopolymer composite material as well as preparation method and application thereof

By using low-carbon and high-performance self-perceptual geopolymer composite materials in cement-based self-perceptual concrete, using alkaline excitation reaction and carbon fiber doping to form multi-conductive channels, the problems of poor compatibility of traditional materials and high filler doping are solved, and high-performance and low-cost self-perceptual concrete are achieved.

CN119750962AInactive Publication Date: 2025-04-04NORTH CHINA ELECTRIC POWER UNIV

Patent Information

Application Number
CN202411755622.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional cement-based self-perceptual concrete has poor compatibility with added conductive phase materials, and there is a problem of dispersion difficulties, and a high filler dosage is required to have good conductivity and perception.

Method used

Low-carbon and high-performance self-perceptual geopolymer composite materials are used, and the raw materials include alkaline exciters, standard sand, iron tailings sand, silicon-aluminum mineral gelling materials, chopped carbon fibers, water, water reducers and dispersants. Through alkaline excitation reactions and doping of carbon fibers, multiple conductive channels are formed to improve perceptual performance.

Benefits of technology

The synergistic or multi-scale effect of multi-conductive channels is achieved, which improves perceived stability and conductivity, reduces the requirements for carbon fiber dosage, saves costs, and improves the integrity, impermeability and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750962A_ABST
    Figure CN119750962A_ABST
Patent Text Reader

Abstract

The invention discloses a self-sensing geopolymer composite material, and belongs to the technical field of intelligent cement base material preparation. The raw materials comprise an alkaline exciting agent, standard sand, iron tailing sand, a silicon-aluminum mineral cementing material, short carbon fibers, water, a water reducing agent and a dispersing agent. The self-sensing geopolymer composite material has multiple conductive phases which can generate a composite effect which is not possessed by a single conductive phase when being used together, multiple conductive channels can generate a synergistic or multi-scale effect (long and short range synergistic conduction), the sensing stability (repeatability) is good, the noise is low, and the self-sensing geopolymer composite material has good application prospects. The requirement for the carbon fiber mixing amount when the conductive seepage threshold value is reached and the threshold value are optimized to a certain degree, and the cost can be saved. When the device is applied to tunnel engineering reinforcement of lining segments and sprayed concrete, a tunnel supporting effect can be achieved, damage of a tunnel structure can be sensed, sensing performance is achieved without additional sensing materials / devices, nondestructive testing of the structure is achieved, and therefore the safety of the structure is improved, and the service life of the structure is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of intelligent cement substrate preparation, and specifically to a low-carbon, high-performance, self-sensing geopolymer composite material and a preparation method and application thereof. Background Art

[0002] As the service environment of modern engineering structures becomes increasingly complex, the demand for real-time intelligent monitoring and evaluation of structural health is becoming increasingly urgent. Self-sensing mortar is a conductive-based sensing material with a similar sensing mechanism to traditional resistance strain gauges. It can sense its own stress / strain / internal damage under the action of external forces, without the need to bury sensors, and can be used for health monitoring of concrete structural components. As a composite material, the internal structure of intrinsic self-sensing concrete can be divided into three phases: the matrix phase composed of traditional concrete materials, the filling phase composed of fillers, and the interface phase between the two. The matrix phase itself has a high resistivity and does not have sensing properties, so the filler phase and the interface phase dominate the conductivity and sensing properties of the composite material.

[0003] Traditional cement-based self-sensing concrete has poor compatibility with added conductive phase materials, and almost all of them have the problem of difficult dispersion, such as carbon fiber, graphene, carbon nanotubes, and stainless steel microfilaments. And because the addition of aggregates, especially coarse aggregates (non-conductive aggregates), will cut off the conductive path, a composite material with a higher filler content is required to have good conductivity and perception. Compared with traditional cement concrete self-sensing mortar, the pore solution of alkali-activated geopolymer materials contains abundant ions (such as sodium ions, hydroxide ions, silicate ions, etc.), so it will have better conductivity, and the conductive phase filler content required to reach the conductive percolation threshold is less. In addition, solid waste iron tailings are selected to replace part of the natural river sand as part of the conductive phase, and carbon fibers are added to the matrix material of the self-sensing mortar prepared by alkali-activated geopolymers, which can not only further improve its greenness, but also play a role in improving the structure of the interface area, strength, impermeability and durability. Based on the above content, the present invention proposes a composite self-sensing geopolymer and its preparation method and application. Summary of the invention

[0004] 1. Technical Problems to be Solved by the Present Invention

[0005] The purpose of the present invention is to propose a low-carbon, high-performance self-sensing geopolymer composite material and its preparation method and application to solve the problems raised in the background technology. The self-sensing geopolymer composite material prepared by the present invention has multiple conductive phases, which can produce a composite effect that a single conductive phase does not have when used together. Multiple conductive channels can produce synergistic or multi-scale effects (long- and short-range synergistic conduction), with good sensing stability (repeatability) and low noise. The requirements for the carbon fiber content and the threshold value when reaching the conductive percolation threshold are optimized to a certain extent, and can save costs.

[0006] 2. Technical solution

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A low-carbon high-performance self-sensing geopolymer composite material, the raw materials of which include: alkaline activator, standard sand, iron tailings sand, silicon-aluminum mineral gelling material, short-cut carbon fiber, water, water reducing agent, and dispersant;

[0009] The raw materials are calculated by mass: 400-800 parts of standard sand, 100-200 parts of iron tailings sand, 250-400 parts of silica-alumina mineral cementitious material, 200-300 parts of alkaline activator, 2-7 parts of chopped carbon fiber, 0.5-2 parts of water reducer, 0-2 parts of dispersant, and no accelerator is required.

[0010] Preferably, the silica-alumina mineral cementitious material includes, but is not limited to, a high-polymer aluminosilicate mineral cementitious material obtained by geopolymerization of metakaolin, blast furnace slag powder, fly ash, carbide slag and coal gangue under the action of an alkali metal ion activator.

[0011] The low-carbon, high-performance, self-sensing geopolymer composite material proposed in the present invention uses iron tailings sand as raw material, which can effectively solve the tailings storage safety problems and environmental pollution problems, and further promote the high-quality development of the construction industry.

[0012] The present invention further protects a method for preparing a low-carbon, high-performance, self-sensing geopolymer composite material, comprising the following steps:

[0013] S1. Weigh the corresponding quality standard sand, iron tailings sand and silicon-aluminum mineral cementitious materials according to the mix ratio requirements, mix them and slowly dry-mix them to form a mineral mixture;

[0014] S2. Prepare the required alkaline activator, add the required carbon fiber into the prepared alkaline activator, and then add the dispersant and water reducer and stir well;

[0015] S3. Slowly introduce the alkaline activator mixed with carbon fiber in S2 into the mineral mixture prepared in S1, place it in a mixer and mix it thoroughly to obtain a self-sensing geopolymer composite material.

[0016] The present invention further protects the use of the above self-sensing geopolymer composite material in lining segments and shotcrete in tunnel engineering reinforcement.

[0017] 3. Beneficial effects

[0018] (1) The low-carbon, high-performance self-sensing geopolymer composite material proposed in the present invention has strong integrity, is not prone to cracks, has good impermeability, and has excellent toughness and durability. It can be widely used in the field of tunnel reinforcement, and can be further used to make lining segments or sprayed concrete to reinforce tunnels. It can also be used as an overall sensor to monitor the overall health status of the tunnel during the construction and operation stages to ensure structural safety, which has positive significance for promoting the high-quality development of the geotechnical industry.

[0019] (2) The low-carbon, high-performance self-sensing geopolymer composite material of the present invention can play a role in tunnel support and sense the damage existing in the tunnel structure itself. It has sensing performance without the need for additional sensing materials / devices, and realizes non-destructive testing of the structure, thereby improving its safety and lifespan. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is an overall flow chart of the method for preparing the low-carbon, high-performance self-sensing geopolymer composite material proposed in Example 1 of the present invention. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described in detail below. The detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the art without creative work are within the scope of protection of the present invention.

[0021] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0022] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0023] Embodiment 1:

[0024] This example provides a low-carbon, high-performance geopolymer self-sensing composite material, and the raw material ratio is as follows:

[0025] The mass of raw materials contained in each cubic meter are: 512kg standard sand, 128kg tailings sand, 192kg metakaolin, 128kg blast furnace slag powder, 166.5kg water glass, 16.4kg solid NaOH particles, 7kg chopped carbon fiber, 95kg water, 1.6kg naphthalene-based high-efficiency water reducer, and 0.96kg methyl cellulose.

[0026] The preparation method of the composite material is implemented according to the following steps:

[0027] Step 1: Weigh the corresponding mass of aggregate and silica-alumina mineral cementitious material according to the required mix ratio, mix them and slowly dry-mix them to form a mineral mixture.

[0028] Step 2: Prepare highly active excitation components, dissolve NaOH particles in water, then add water glass and stir thoroughly.

[0029] Step 3: Add the required carbon fiber, add the dispersant and water reducer and stir thoroughly. Finally, slowly introduce the alkali activator mixed with the carbon fiber into the mixture, place it under a mixer and mix thoroughly to obtain the required self-sensing geopolymer composite material.

[0030] Construction method: Arrange electrodes at equal intervals on the top plate or annularly arranged in the tunnel rock surface after excavation, and spray the prepared fresh geopolymer concrete onto the tunnel rock surface after excavation through the spraying pipe using the tunnel wet spraying process. The connecting wires are encapsulated with epoxy resin. The fresh geopolymer sprayed concrete completes initial setting in 5 minutes, and continues to spray to keep it in a moist state for no less than 7 days to form initial support on the tunnel rock surface.

[0031] Embodiment 2:

[0032] This example provides a low-carbon, high-performance geopolymer self-sensing composite material, and the raw material ratio is as follows:

[0033] The mass of raw materials contained in each cubic meter are: 512kg standard sand, 128kg tailings sand, 192kg metakaolin, 128kg blast furnace slag powder, 137kg water glass, 16kg solid NaOH particles, 7kg chopped carbon fiber, 80kg water, 1.6kg naphthalene-based high-efficiency water reducer, and 0.96kg methyl cellulose.

[0034] The preparation method of the composite material is implemented according to the following steps:

[0035] Step 1: Weigh the corresponding mass of aggregate and silica-alumina mineral cementitious material according to the required mix ratio, mix them and slowly dry-mix them to form a mineral mixture.

[0036] Step 2: Prepare highly active excitation components, dissolve NaOH particles in water, then add water glass and stir thoroughly.

[0037] Step 3: Add the required carbon fiber, add the dispersant and water reducer and stir thoroughly. Finally, slowly introduce the alkali activator mixed with the carbon fiber into the mixture, place it under a mixer and mix thoroughly to obtain the required self-sensing geopolymer composite material.

[0038] Construction method: Arrange electrodes at equal intervals on the top plate or annularly on the rock surface of the tunnel after excavation, and spray the prepared fresh geopolymer concrete onto the rock surface of the tunnel after excavation through the spraying pipe using the tunnel wet spraying process. The connecting wires are encapsulated with epoxy resin. The fresh geopolymer sprayed concrete completes initial setting in 5 minutes, and continues to spray to keep it in a moist state for no less than 7 days to form initial support on the tunnel rock surface.

[0039] Embodiment 3:

[0040] This example provides a low-carbon, high-performance geopolymer self-sensing composite mortar, and the raw material mix ratio is as follows:

[0041] The mass of raw materials contained in each cubic meter are: 512kg standard sand, 128kg tailings sand, 192kg metakaolin, 128kg blast furnace slag powder, 130.5kg water glass, 17.3kg solid NaOH particles, 7kg chopped carbon fiber, 98kg water, 1.6kg naphthalene-based high-efficiency water reducer, and 0.96kg methyl cellulose.

[0042] The preparation method of the composite material is implemented according to the following steps:

[0043] Step 1: Weigh the corresponding mass of aggregate and silica-alumina mineral cementitious material according to the required mix ratio, mix them and slowly dry-mix them to form a mineral mixture.

[0044] Step 2: Prepare highly active excitation components, dissolve NaOH particles in water, then add water glass and stir thoroughly.

[0045] Step 3: Add the required carbon fiber, add the dispersant and water reducer, and stir thoroughly. Finally, slowly introduce the alkali activator mixed with the carbon fiber into the mixture, place it under a mixer and mix thoroughly to obtain the self-sensing geopolymer composite material.

[0046] Construction method: Pre-embed parallel electrodes before pouring, and use epoxy resin to encapsulate the connecting wires after they are led out. The prepared freshly mixed geopolymer concrete is introduced into the mold and vibrated to make it dense. After forming, it is demoulded and the standard curing is not less than 28 days.

[0047] Embodiment 4:

[0048] This example provides a low-carbon, high-performance geopolymer self-sensing composite material, and the raw material ratio is as follows:

[0049] The mass of raw materials contained in each cubic meter is: 512kg standard sand, 128kg tailings sand, 192kg metakaolin, 128kg blast furnace slag powder, 183kg water glass, 24.2kg solid NaOH particles, 7kg chopped carbon fiber, 74kg water, 1.6kg naphthalene-based high-efficiency water reducer, and 0.96kg methyl cellulose.

[0050] The preparation method of the composite material is implemented according to the following steps:

[0051] Step 1: Weigh the corresponding mass of aggregate and silica-alumina mineral cementitious material according to the required mix ratio, mix them and slowly dry-mix them to form a mineral mixture.

[0052] Step 2: Prepare highly active excitation components, dissolve NaOH particles in water, then add water glass and stir thoroughly.

[0053] Step 3: Add the required carbon fiber, add the dispersant and water reducer, and stir thoroughly. Finally, slowly introduce the alkali activator mixed with the carbon fiber into the mixture, place it under a mixer and mix thoroughly to obtain the self-sensing geopolymer composite material.

[0054] Construction method: Pre-embed parallel electrodes before pouring, and use epoxy resin to encapsulate the connecting wires after they are led out. The prepared freshly mixed geopolymer concrete is introduced into the mold and vibrated to make it dense. After forming, it is demoulded and the standard curing is not less than 28 days.

[0055] Comparative Example 1:

[0056] The difference from Example 1 is that the raw material components do not contain iron tailings sand.

[0057] Comparative Example 2:

[0058] The difference from Example 2 is that the gelling material is replaced by cement.

[0059] The types and weights of raw materials required for preparing the composite materials in the above embodiments and comparative examples are summarized. Please refer to the following Table 1 and Table 2 for details.

[0060] Table 1

[0061]

[0062] Table 2

[0063]

[0064] Performance Test:

[0065] The environmentally friendly self-sensing concrete prepared in each embodiment and comparative example was poured and cured, and the mechanical strength and electrical properties of the concrete were tested after reaching the curing age. The test results are shown in Table 3.

[0066] Table 3

[0067] serial number Compressive strength(MPa) Flexural strength(MPa) <![CDATA[Conductivity 10 -2 (Ω·cm) -1 > Example 1 59.784 7.72 1.75452 Example 2 55.864 8.45 1.5733 Example 3 56.845 6.7 1.74442 Example 4 63.7 7.59 1.38912 Comparative Example 1 51.3 6.986 1.2734 Comparative Example 2 43.32 6.812 0.242

[0068] It can be seen from Table 3 that the compressive strength of the low-carbon, high-performance self-sensing geopolymer composite material prepared by the present invention can reach 63.7Mpa. The compressive strength of the basic self-sensing composite material prepared in Comparative Examples 1 and 2 is lower than the compressive strength of the self-sensing composite material with the addition of tailings sand and geopolymer. At the same time, it can also be seen that the addition of iron tailings sand promotes the conductive phase of the self-sensing mortar. At the same time, the modulus and sol ratio of the alkaline activator when preparing the geopolymer have a great influence on the strength and conductive properties of the self-sensing mortar.

[0069] The self-sensing geopolymer composite material of the present invention has excellent performance, saves costs while achieving high-quality utilization of resources, and further promotes the sustainable development of the construction industry.

[0070] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and improved concepts of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.

Claims

1. Low-carbon, high-performance, self-sensing geopolymer composite material, characterized in that: The raw materials include: alkaline activator, standard sand, iron tailings sand, silica-alumina mineral cementitious material, short-cut carbon fiber, water, water reducing agent, dispersant; The raw materials are calculated by weight: 400-800 parts of standard sand, 100-200 parts of iron tailings sand, 250-400 parts of silicon-aluminum mineral cementitious material, 200-300 parts of alkaline activator, 2-7 parts of short-cut carbon fiber, 0.5-2 parts of water reducing agent, and 0-2 parts of dispersant.

2. The low-carbon, high-performance, self-sensing geopolymer composite material according to claim 1, characterized in that: The silica-alumina mineral gelling material comprises: a high-poly aluminosilicate mineral gelling material obtained by geopolymerization reaction of metakaolin, blast furnace slag powder, fly ash, carbide slag and coal gangue under the action of an alkali metal ion activator.

3. A method for preparing a low-carbon, high-performance, self-sensing geopolymer composite material as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Weigh the corresponding quality standard sand, iron tailings sand and silicon-aluminum mineral cementitious materials according to the mix ratio requirements, mix them and slowly dry-mix them to form a mineral mixture; S2. Prepare the required alkaline activator, add the required carbon fiber into the prepared alkaline activator, and then add the dispersant and water reducer and stir well; S3. Slowly introduce the alkaline activator mixed with carbon fiber in S2 into the mineral mixture prepared in S1, place it in a mixer and mix it thoroughly to obtain a self-sensing geopolymer composite material.

4. Application of the low-carbon, high-performance, self-sensing geopolymer composite material as described in any one of claims 1-2 in lining segments and shotcrete in tunnel engineering reinforcement.

Citation Information

Patent Citations

  • Carbon fiber / alkali activation composite pressure-sensitive material and method for preparing same

    CN109081643A

  • Geopolymer-based self-induction anchor rod mortar and preparation method thereof

    CN110981295A

  • Iron tailing large-slump high-strength conductive concrete and preparation method thereof

    CN112521076A

  • Self-sensing high performance fiber reinforced geopolymer composites

    US20190031563A1

  • KR20210055986A

Cited By

  • Damage self-sensing geopolymer coating and preparation and application methods thereof

    CN121249185A

  • Preparation method of functionalized geopolymer aggregate reinforced ultrahigh-ductility cement-based composite material

    CN121894953A

  • A method for preparing a functionalized geopolymer aggregate reinforced ultra-high ductility cementitious composite

    CN121894953B

  • Intelligent sensing geopolymer concrete sensor and preparation method and application thereof

    CN122301503A